Sustainability Consciousness and Creativity in Education: Evidence, Gaps, and a Research Agenda, with Implications for Science Education - Muhammad Fuad Sya'ban; Adi Rahmat; Siti Sriyati; Omay Sumarna (Gawi: Journal of Action Research, 2026)
Education for sustainability requires learners who are both conscious of sustainability and able to generate creative responses to complex socio-ecological problems, yet how these two capacities relate remain unclear and scattered across disconnected studies. This systematic review synthesized empirical research on the relationship between sustainability consciousness and student creativity in formal secondary-to-tertiary education. Following PRISMA 2020, Scopus and Web of Science were searched (2015–2026); records were screened in two stages, appraised with the Mixed Methods Appraisal Tool, and combined through thematic synthesis. Eleven studies met the criteria. Across diverse subjects and countries, the two constructs were consistently and positively associated, although the reported direction varied sustainability consciousness predicting creativity, creativity predicting sustainability consciousness, and the two co-developing under shared interventions. However, sustainability was operationalized inconsistently, no study employed the full tripartite sustainability-consciousness construct, and cross-sectional designs precluded causal inference. The review exposes a fragmented evidence base and the absence of an integrative framework. It calls for mechanism-based, longitudinal designs that align comprehensive sustainability-consciousness and creativity measures, and recommends active, integrative pedagogies for cultivating both capacities across diverse subjects, with particular relevance for science education.